Modular Dynamic Modeling for On-Orbit Assembly of Large-Scale Space Structures - Weiya Zhou; Shunan Wu; Jinzhao Yang (International Journal of Aerospace Engineering)
The large-scale space structure during on-orbit assembly is a time-varying system. The dynamic modeling problem of such incrementally increasing space structure is investigated, and a modular dynamic modeling approach is proposed in this paper. The dynamic model of each substructure is first established, and then, a database is designed to store substructure models, which is used for subsequent dynamic modeling in the assembly process. The fixed connection relationship between adjacent substructures is described by constraint conditions, which lead to the coefficient matrices of adjacent substructures being decoupled. The substructures are assembled in a given sequence, and then, the dynamic modeling, to describe the large-scale space structure on-orbit assembly, is gradually completed via using the proposed modeling approach. The numerical simulation is finally presented. The results demonstrate that the extra calculation resulting from the coefficient matrices coupling of adjacent substructures is avoided. Moreover, the proposed dynamic model can accurately describe the dynamic characteristics of the large-scale space structure during on-orbit assembly.